The Representation of Emotional Framework in Nicole Album by NIKI (2022) - Ade Dwi Wahyu Ananda Sitepu; Vadelia Diah Susanti; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Abstract This research explores the emotional representation found in NIKI’s album Nicole (2022) by utilizing Paul Ekman’s Basic Emotions Theory to examine how grief, anger, fear, disgust, happiness, and surprise are articulated through the lyrics. Employing a qualitative descriptive design alongside content analysis, the study scrutinizes words, phrases, metaphors, and narrative tones drawn from six tracks: Backburner, Oceans & Engines, The Apartment We Won’t Share, Autumn, Anaheim, and Take a Chance with Me. The results indicate that emotional expressions within the album do not exist in isolation; rather, they create a cohesive emotional trajectory that evolves from attachment, longing, and internal conflict to acceptance and self-reflection. Linguistic characteristics especially metaphorical language and shifts in tone act as crucial indicators that shape the album’s emotional richness, demonstrating how contemporary music serves as both a literary and psychological medium. This study adds to the limited collection of album level emotional analyses by showing that Ekman’s framework, although initially intended for facial expressions, is still highly applicable for interpreting emotional significance in song lyrics. Furthermore, the research points out a deficiency in prior scholarship, which often concentrates on single-track analysis or Western-centric datasets, thereby leaving Southeast Asian contemporary albums insufficiently examined. While the study effectively outlines the emotional framework of the album, it is confined to lyrical elements and does not consider musical or auditory aspects. Future investigations are recommended to integrate multimodal features to offer a more thorough understanding of emotional representation in contemporary music.